Influence of variability and association on essential oil content of German chamomile (Chamomilla recutita (L.) Rauschert) - Sharma, R K Lal, J R Sharma, S (Journal of Spices and Aromatic Crops, 2000)
The nature and extent of variability, association, co-heritability and path coefficients were studied for 8 economic traits in 48 accessions of German chamomile (Chamomilla recutita) assembled from India and abroad. The genotypic correlations were higher than phenotypic correlations for all the traits except dry flower yield, oil content and branches per plant. Fresh flower yield was significantly and positively correlated with branches per plant, dry flower yield, spread area and oil yield at both genotypic and phenotypic levels. Oil content and dry flower yield were also associated with oil yield. All the traits exhibited high heritability, the highest being spread area and lowest for oil content. The genetic advance over mean was the highest for oil yield and lowest for spread area. Th. highest direct contribution to essential oil yield was by fresh flower yield (0.335) followed by oil content (0.286), plant height (0.144), dry flower yield (0.050) and spread area (0.013), respectively. Dry flower yield indirectly contributed maximum to essential oil yield. The correlations between plant height and oil content had the maximum co-heritability value (1.306) followed by days to flower (50%) with dry flower yield (1.186) and plant height (1.129). These traits may form a good selection criterion for improvement of essential oil yield in German chamomile.